Linguistic and Medical Aspects in Health Care. Focus on Dementia. - (:unkn) unknown (University of Latvia Press, 2024)
The collective monograph reveals dementia as an element of public discourse, an object of interdisciplinary research encompassing the fields of medicine, linguistics, and discursively – social sciences; dementia is considered from a medical perspective and in the context of social care. The findings and conclusions indicate that it is necessary to establish collaborative, interdisciplinary research on dementia in the Baltic states to provide optimal support to the patients in the future and to find far-reaching socially responsible solutions.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics::Linguistic subjects::Linguistics; Frontotemporal Degeneration; Diagnostic Challenges of Alzheimer’s Disease; Dementia; Linguistics and Medicine; Aspekte des Gesundheitswesens in Lehrbüchern für Deutsch als Fremdsprache; Verwendung der Bezeichnungen für Demenz; Sensitive memory work